Steel Jacketing : A Review - Kumar, Gaurav (AMC Indian Journal of Civil Engineering, 2024)
Steel Jacketing is a widely adopted retrofitting technique in India to enhance the structural integrity and load-bearing capacity of reinforced concrete (RC) columns and foundations, particularly in aging infrastructure and seismically vulnerable regions. This method involves encasing existing columns or foundations with steel plates or sections, which are then bonded to the original structure using epoxy or mechanical fasteners. The steel jacket acts as a confining mechanism, improving the structural performance under axial, lateral, and seismic loads. In the Indian context, where many structures were built without adherence to modern seismic codes, steel jacketing offers a cost-effective and efficient solution to mitigate the risks of collapse during earthquakes. Additionally, it is particularly suitable for regions with high humidity and varying temperatures, as steel provides durability and resistance to environmental degradation. This paper discusses the procedure of steel jacketing.